ANALSIS ORGANISASI DAN MANAJEMEN UNIVERSITAS SATYA NEGARA INDONESIA (USNI) - Siagian, Arifin (Pasca Sarjana Universitas Satya Negara Indonesia, 2016)
The organization of USNI orientates to the goal, therefore the structure and the design of the organization also orientates to the goal. The principal of USNI should conceive the structure a tool of contribution for reaching the goal of USNI effectively. The prinsipal of USNI should also notice several factors i.e. technology, the characteristic of job, lecturers and employees, environmental requirement, the importance of accepting and processing the information from environment and whole strategy which been choosen to reach the goal of USNI.